Film (de)construction of national identity. The case of Serbian films from the 1990s - Zvijer, Nemanja (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2018)
The article deals with the relation between films and the concept of the national identity. These issues are discussed on the example of Serbian cinema in the 1990s. Using Anthony Smith’s approach to the visual representation of national identity, the ways in which films in Serbia construct national identity is discussed. After that, several films are analyzed that critically question the concept of nationalism. This analysis demonstrates how ideology, in this particular case, nationalistic ideology, at the semantic level can be related to films, one of the most influential segments of popular culture.